Lighting up lives through cooking gas and transforming society - Barua, S. K. (Samir K.); Agarwalla, Sobhesh Kumar (London : Indian Institute of Management, Ahmedabad, 2020)
Cases of the Indian Institute of Management Ahmedabad are prepared as a basis for class discussion. Cases are not designed to present illustrations of either correct or incorrect handling of administrative problems.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social change; Gas cooking